PERBANDINGAN COMPUTER VISION SYNDROME PADA MAHASISWA FAKULTAS KEDOKTERAN YANG MELAKUKAN DIET VEGETARIAN DAN NON VEGETARIAN - Abimanyu Putera Yudha (2022)
Computer Vision Syndrome (CVS) is a set of eye symptoms at high risk for students due to the increased use of digital devices. At this time, various forms of diet can affect visual function. This study aims to determine the effect of a vegetarian diet on CVS in students of the Faculty of Medicine, Universitas Pembangunan Nasional Veterans Jakarta, Academic Year 2021/2022. This study uses a case-control design. The sample size is 40 students divided into vegetarian and non-vegetarian groups. Data were collected using Computer Vision Syndrome Questionnaire and Purposive Sampling. Data were analyzed using the Chi-Square test and independent t-test. The results showed that as many as 24 of 40 subjects (60%) experienced CVS. The test results showed that there was no difference in the incidence of CVS (p = 0.333) and the severity of CVS (p = 0.237) in the vegetarian and non-vegetarian groups, but there were differences in symptoms of watery eyes (p = 0.027; OR = 0.184; CI = 0,047  0,710) and headache symptoms (p = 0.027). = 0.010; OR = 0.118; CI = 0,026  0,537) in both groups. Vegetarian and non-vegetarian diets each benefit visual function, affecting CVS symptoms differently. It is necessary to research to determine the effect of nutrient intake on CVS. Keywords: Computer Vision Syndrome, Vegetarian Diet, College Student